Factors Influencing SME Performance: The Mediating and Moderating Role of Perceived Social Media Benefit and Organizational Culture - Saeed Khalifan RASHEED GHANEM; Nor Aziati Abdul Hamid (Communications of International Proceedings, 2021)
The study sought to investigate the mediating and moderating role of social media and organizational culture in the relationship between the Technology–organization–environment (TOE) framework and SME performance. Using a quantitative research design and positivist research paradigm, the researcher sought to attain the study's research objectives. A sample of 452 respondents consisting of SME business owners, CEO and top management were selected from each of the seven districts in the UAE. The study recorded a 92.9% response rate as only 420 questionnaires were useable for data analysis. Data were analyzed using descriptive statistics and the Partial Least Squares structural equation modelling. The study revealed that the technological context positively and significantly affects SME performance, whereas the organizational and environmental context does not affect SME performance. Findings also revealed that social media benefit positively influenced SME performance directly. Regarding the mediating role of social media between the TOE framework and SME performance a positive and significant effect was found. However, a negative relationship was found regarding the moderating effect of organizational culture on social media benefit and SME performance. This result may be because it is difficult to separate between different culture types within SMEs. An organization usually has its values and customs, which translates into the organizational culture that all employees are expected to imbibe and practice. Hence, if an organization is mono-culturalist, its organizational culture may have no influence on how social media is adopted and, consequently, SME performance. The study concludes with recommendations for further study and addresses some limitations in the study's design.
Keywords: SME performance; perceived social media benefit; organizational culture